PENGARUH MODEL PEMBELAJARAN KONTEKSTUAL UNTUK MENINGKATKAN HASIL BELAJAR MATERI PECAHAN KELAS III SEKOLAH DASAR - Fifi Dwi Jayanti; Rayi Siti Fitriani; Wina Mustikaati (STKIP Subang, 2026)
This study aims to determine the effect of the Contextual Teaching and Learning (CTL) model on the learning outcomes of third-grade elementary school students in fraction material, covering differences in learning outcomes before and after the implementation of the model, as well as differences in the improvement of learning outcomes between the experimental and control classes. The study employed a quantitative approach using a quasi-experimental method with a nonequivalent control group design. The research sample consisted of 47 third-grade students of SDN 1 Cianting Utara in the 2025/2026 academic year, comprising 25 students in the experimental class who received learning using the CTL model and 22 students in the control class who received conventional learning. The research instrument was a fraction learning outcome test consisting of 9 valid and reliable items (reliability coefficient of 0.77) selected from 20 trial items. Data were analyzed using the Shapiro-Wilk normality test and the nonparametric Mann-Whitney U hypothesis test with the assistance of SPSS 27. The results showed that prior to treatment, there was no significant difference in learning outcomes between the two classes (Sig. = 0.459 > 0.05), with pretest averages of 19.80 (experimental) and 18.00 (control). After treatment, the posttest average of the experimental class increased to 98.24 and the control class to 69.55, showing a significant difference (Sig. = 0.001 < 0.05). The gain in learning outcomes of the experimental class (78.44) was also significantly higher than that of the control class (51.50) (Sig. = 0.000 < 0.05). Thus, the contextual teaching and learning model was proven to have a significant effect and to be more effective in improving students' learning outcomes on fraction material compared to conventional learning. Keywords: contextual teaching and learning model, learning outcomes, fractions, elementary school